Intellectual property protection in VLSI designs" theory and practice - Qu, Gang; Potkonjak Miodrag (Boston: Kluwer Academic, 2003)
It provides an overview of the security problems in modern VLSI design with a detailed treatment of our newly developed constraint-based protection paradigm for the protection of VLSI design IPs from FPGA design to standard-cell placement, from high-leve
Keywords: Intellectural property protection; VLSI designs